2017
DOI: 10.1007/s11136-017-1533-5
|View full text |Cite
|
Sign up to set email alerts
|

Examining health-related quality of life patterns in women with breast cancer

Abstract: Purpose We aimed to identify subgroups of women with breast cancer who experience different health-related quality of life (HRQOL) patterns during active treatment and survivorship and determine characteristics associated with subgroup membership. Methods We used data from the third phase of the population-based Carolina Breast Cancer Study and included 2,142 women diagnosed with breast cancer from 2008–2013. HRQOL was measured, on average, 5- and 25-months post-diagnosis. Latent profile analysis was used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 51 publications
1
20
0
2
Order By: Relevance
“…Previous work has shown that women with breast cancer may experience impaired physical and emotional functioning after cancer treatment 12‐24 . Several demographic and clinical determinants may negatively influence survivors' HRQOL 12‐18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that women with breast cancer may experience impaired physical and emotional functioning after cancer treatment 12‐24 . Several demographic and clinical determinants may negatively influence survivors' HRQOL 12‐18 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that women with breast cancer may experience impaired physical and emotional functioning after cancer treatment 12‐24 . Several demographic and clinical determinants may negatively influence survivors' HRQOL 12‐18 . For instance, breast cancer survivors with comorbid conditions, such as heart failure, 19 arthritis, 13,20 diabetes, 13 and lymphedema, 20,21 have poorer physical and mental health outcomes than those without these conditions 20,22‐24 .…”
Section: Introductionmentioning
confidence: 99%
“…Com relação à sobrevivência, é imprescindível assinalar que Samuel et al (2016), Pinheiro et al (2016), Pinheiro et al (2017), Vadaparampil et al (2017) e Claridy, Ansa, Damus, Alema-Mensah e Smith (2018) não concordaram quanto aos parâmetros temporais referentes a essa etapa da experiência oncológica. Seus estudos acataram desde o período de recebimento do diagnóstico até um período indeterminado que pode ser confundido com o próprio ciclo vital da paciente.…”
Section: Resultsunclassified
“…This group displayed high education attainment, but the impact of socioeconomic status on QOL and information needs across other studies is inconclusive. [45][46][47] Although one participant did not complete the second interview, data saturation was met and findings were verified by the participants. Maximum variation improved sample heterogeneity, but a larger sample may have yielded additional findings.…”
Section: Limitationsmentioning
confidence: 99%